Effects of freezing-microwave assisted alkali treatment on physicochemical and thermomechanical properties of bamboo - Beilong Zhang; Xiaolan Yin; Haixia Yu; Zhiqiang Zhang; Weilian Qin; Xiu Hao (Polymer Testing, 2025)
The high lignin content and longitudinally arranged fibers endow bamboo with high hardness and brittleness, but also make it difficult for bamboo to bend or form during processing. To address the above problem, this study presents a treatment method based on freezing or freezing-microwave assisted alkali — sodium hydroxide (NaOH) or calcium oxide (CaO) — softening bamboo, and enhances bamboo stability by adding polyethylene glycol (PEG-4000). The softened bamboo was characterized using chromaticity analysis, microscopic morphology, X-ray diffraction, dynamic mechanical analysis, and contact angle measurement. The treatment of freezing followed by microwaving effectively promoted the hydrolysis of hemicellulose, reduced the crystallinity of bamboo, and increased the contact angle significantly. Therefore, freezing-microwave treatment could better improve the hydrophobic properties of bamboo. The decrease in storage modulus (E′) is an important index to measure the decline in bamboo rigidity. The E′ of NaOH impregnated bamboo decreased from 5159.45 to 314.80 MPa during the freezing-microwave assisted treatment. In contrast, the E′ of calcium hydroxide (Ca(OH)2) impregnated bamboo decreased from 3434.21 to 125.35 MPa. The results indicate the saturation characteristics of the Ca(OH)2 solution better balance the alkali concentration. This mild alkaline environment caused little damage to the internal structure, and better retained the fiber strength and overall stability of bamboo. Notably, the waste liquid of Ca(OH)2 can react with carbon dioxide, and its raw material, CaO, has low cost and a simple production process. This advantage promotes the concept of sustainable development of green environmental protection.